Experimental investigation of cost-effective ZnO nanofluid based spectral splitting CPV/T system. (1st March 2020) - Huaxu, Liang; Fuqiang, Wang; Dong, Zhang; Ziming, Cheng; Chuanxin, Zhang; Bo, Lin; Huijin, Xu
Abstract: Nanofluid-based spectral splitting concentrating photovoltaic thermal (CPV/T) system enables photovoltaic (CPV) cells and thermal absorbers to operate at different temperatures and realizes the utilization of full-spectrum sunlight. It is important to find one kind of low cost nanofluid that can be applied to nanofluid-based spectral splitting CPV/T system. In this study, the feasibility of using cost-effective glycol-ZnO nanofluid in spectral splitting CPV/T system was experimentally verified. A two-axis sun-tracking nanofluid-based spectral splitting CPV/T system was designed and fabricated. The solar energy conversion efficiency correlation coefficient was utilized to compare the thermodynamic performance of glycol-ZnO nanofluid-based spectral splitting CPV/T system with those of water-polypyrrole and water-Ag-SiO2 nanofluid-based spectral splitting CPV/T system. The effects of ZnO nanoparticles concentration in glycol-ZnO nanofluid on thermal and electrical performances were investigated. The cost comparisons of different types of nanoparticles were also conducted. The results indicated that the correlation coefficient of glycol-ZnO nanofluid-based spectral splitting CPV/T system was 0.218 and 0.05 higher than those of water-polypyrrole and water-Ag-SiO2 nanofluid-based spectral splitting CPV/T system, respectively. The cost of ZnO nanoparticles was 0.13%, 0.08% and 0.17% of cost of Au, Ag and polypyrrole nanoparticles, respectively. Highlights: . Using cost-effective ZnO nanofluid in splitting CPVT was experimentally verified. . ZnO nanofluid has better performance in CPVT than polypyrrole & Ag–SiO2 nanofluid. . ZnO nanofluid has big cost advantage than reported nanofluid in CPVT system.